2005
DOI: 10.1590/s0100-41582005000100016
|View full text |Cite
|
Sign up to set email alerts
|

Response of cucurbit species to Rotylenchulus reniformis

Abstract: The state of Rio Grande do Norte is the major melon (Cucumis melo) producer in Brazil and the reniform nematode Rotylenchulus reniformis has become increasingly important due to damages to that crop and the lack of resistant cultivars and effective control measures. Under these circumstances, eight cucurbit genotypes were screened for resistance or tolerance to a population of R. reniformis in naturally infested field soil, under greenhouse conditions. A high reduction in shoot mass was found in all infected g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In the Southeastern United States, R. reniformis is most commonly known as a pest of cotton (Robinson et al, 2005), but has been shown to infest cultivated watermelon (Robinson et al, 1997). In Brazil, R. reniformis was shown to reproduce on the roots of cucurbit species, reducing aboveground biomass as nematode populations increase (Torres et al, 2005).…”
mentioning
confidence: 99%
“…In the Southeastern United States, R. reniformis is most commonly known as a pest of cotton (Robinson et al, 2005), but has been shown to infest cultivated watermelon (Robinson et al, 1997). In Brazil, R. reniformis was shown to reproduce on the roots of cucurbit species, reducing aboveground biomass as nematode populations increase (Torres et al, 2005).…”
mentioning
confidence: 99%